2013
DOI: 10.3389/fpsyg.2013.00073
|View full text |Cite|
|
Sign up to set email alerts
|

Recursive Fury: Conspiracist Ideation in the Blogosphere in Response to Research on Conspiracist Ideation

Abstract: Conspiracist ideation has been repeatedly implicated in the rejection of scientific propositions, although empirical evidence to date has been sparse. A recent study involving visitors to climate blogs found that conspiracist ideation was associated with the rejection of climate science and the rejection of other scientific propositions such as the link between lung cancer and smoking, and between HIV and AIDS (Lewandowsky et al., in press; LOG12 from here on). This article analyses the response of the climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…Indeed such rituals for CTs often take a reflexive form, providing not only answers to conspiracy-related questions, but also anticipating critique and denigration (e.g., Lewandowsky et al, 2013). Averting the denigration of the ingroup, possibly by outgroup denigration, is then a recurrent CT trope.…”
Section: Explaining Ct Stickiness: Cognitive Science Of Religionmentioning
confidence: 99%
“…Indeed such rituals for CTs often take a reflexive form, providing not only answers to conspiracy-related questions, but also anticipating critique and denigration (e.g., Lewandowsky et al, 2013). Averting the denigration of the ingroup, possibly by outgroup denigration, is then a recurrent CT trope.…”
Section: Explaining Ct Stickiness: Cognitive Science Of Religionmentioning
confidence: 99%
“…The predominant paradigm of psychological research in the field of conspiracy theories assumes that a clear distinction between an official truth and delusive idiosyncratic explanations can be made. For instance, Lewandowsky et al (2013) showed that taking the moon landing for a hoax is correlated with a disbelief in climate change and a rejection of the fact that smoking causes lung cancer. One can either believe that smoking causes lung cancer, or one might not.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from some recent studies—e.g., Sapountzis and Condor (2013) have evaluated the spontaneous use of conspiracy narratives in interviews of Greek citizens and Lewandowsky et al (2013) investigated conspiracist ideation in the blogosphere—most studies have focused on the recipients of conspiracy theories using questionnaires and drawing an artificial red line between believers and disbelievers. To our understanding, this approach reveals some misleading basic assumptions about conspiracy theories: (a) Conspiracy theories are treated as invariant entities (b) that can be reduced to single statements and (c) that recipients of conspiracy theories can be regarded as passive consumers and (d) that believers are always believers independently from the “quality” of the regarding storyline.…”
Section: Introductionmentioning
confidence: 99%
“…Barnum) offer “something for everyone”; so everybody is free to adopt some story fragments only. As we have no further information about and control of the regarding creators, proliferators and consumers of such content we need methods—in addition to content analysis (e.g., Lewandowsky et al, 2013a), interviews (e.g., Sapountzis and Condor, 2013) and standardized questionnaires (e.g., Lewandowsky et al, 2013b)—which allow for the dynamic character of compiling, reframing and linking of information to unfold.…”
Section: Introductionmentioning
confidence: 99%